Estimation of the service load capacity of plain concrete arch bridges using a novel approach: Stress intensity factor. (October 2020) - Panian, René; Yazdani, Mahdi
Abstract: Masonry arch bridges have furnished railway networks as important infrastructures. The evaluation of the behavior of masonry arch bridges has drawn a great deal of attention over the past years due to the increase in the speed of railway fleet, need for augmentation of trains axle loads, and increase in the number of vehicles. These critical structures have been designed for service loads demanded at past times and since service loads are different in the present time, their behavior crucially needs to be assessed. Various analytical, experimental, approximate, and numerical methods have been proposed so far to estimate the residual capacity of masonry arch bridges. The present paper aims to predict the maximum service load of railway plain concrete arch bridges using a new approach with the aid of stress intensity factor in the fracture mechanics. Since stress intensity factor is solved analytically only for highly simple problems, a numerical approach and the finite element method were used in the present paper to calculate this parameter. Finally, given the stress intensity factor and proposing a relation for concrete toughness based on a statistical study, the maximum service load of these vital structures is obtained. To validate the results, two plain concrete arch bridges —located at kilometer 23 and 24 of Tehran-Qom Old Railway— were used. The results revealed that the proposed method has agreed well with the field observations.